Boosting Export Performance - World Bank (Washington, DC, 2022)
Improving Kosovo’s export competitiveness can help to catalyze growth and reduce poverty. As a small economy, Kosovo will benefit from integration, both globally and regionally, to exploit scale economies from access to a larger market. Higher exports will not only contribute to growth and lower current account deficits but can also help heighten productivity due to more innovation and learning by exporting. Exporting firms, which are more competitive, will also be able to create better jobs and economic opportunities for Kosovars. This background note examines export dynamics in Kosovo over the period 2010-19, benchmarking Kosovo against relevant comparator countries. It overviews Kosovo’s trade structure, export dynamics at the firm level, trade policy and regulatory framework, and constraints to trade in goods and services and identifies policy options for consolidating trade growth in growing sectors. The note also spotlights digitalization and digital trade. It analyzes the enabling environment and suggests policies to enhance digital connectivity, improve the regulatory environment for digital trade, and encourage the use of e-payments.